Community owned fibre optic networks - a sustainable broadband future for rural areas in Croatia? - Igor Brusic; Martin Lundborg; Wolfgang Reichl (International Telecommunications Society (ITS), 2010)
For a small rural community such as the city of Krk (6.000 inhabitants), the business model for a fibre roll-out is not very promising if it is based on the classical cost-benefit analysis where investments are covered by service revenue generated. The conducted analysis is leading to two main findings - there will be no network operator investing in the roll-out of a fibre access network in the city of Krk and the fibre net-work has to be rolled out by becoming an integral part of the utility of the city. By util-izing the existing network of empty ducts and the facilities of the city owned cable network, the city of Krk has a better starting position than other comparable cities in Croatia. Public private partnership and open access are highly relevant in future elaborations.
Keywords: 330; optical access networks; community owned; business models; open ac-cess; cost analysis